Obtenção de curvas mestre de compósitos poliméricos estruturais utilizando ensaios dinâmicos mecânicos sob fluência - Rocha, Danielle Ferrari Borges (2010)
The growing advanced composites appliance in aircraft s structural parts has demanded to spread the knowledge about mechanical behavior prediction in longer time periods. In this way, the main purpose of this study is to establish an accelerated test method based on mechanical-dynamical-thermal analysis (DMTA), to predict the mechanical behavior of carbon fiber/epoxy resin composites. The DMTA technique was used on two modes: multi-frequency and creep. In the first case, three point bending tests on dynamical mode did not present a good fitting to built master curves, considering the experimental parameters used. Though, creep tests showed good results. In these tests, parameters used as temperature range from 25ºC to 235ºC and isothermals at every 15ºC for 100 minutes allowed to obtain compliance modulus versus time master curves with a good fitting. From the obtained results, it is possible to conclude that the proposed method presented good adhesion to the basic concept of material viscoelasticity, therefore can be used to predict mechanical behavior of composite materials.